Biological and microbiological interactions of Ti-35Nb-7Zr alloy and its basic elements on bone marrow stromal cells: good prospects for bone tissue engineering - Daphne de Camargo Reis Mello; Lais Morandini Rodrigues; Fabia Zampieri D'Antola Mello; Thais Fernanda Gonçalves; Bento Ferreira; Sandra Giacomin Schneider; Luciane Dias de Oliveira; Luana Marotta Reis de Vasconcellos (SpringerOpen, 2020)
Abstract Background An effective biomaterial for bone replacement should have properties to avoid bacterial contamination and promote bone formation while inducing rapid cell differentiation simultaneously. Bone marrow stem cells are currently being investigated because of their known potential for differentiation in osteoblast lineage. This makes these cells a good option for stem cell-based therapy. We have aimed to analyze, in vitro, the potential of pure titanium (Ti), Ti-35Nb-7Zr alloy (A), niobium (Nb), and zirconia (Zr) to avoid the microorganisms S. aureus (S.a) and P. aeruginosa (P.a). Furthermore, our objective was to evaluate if the basic elements of Ti-35Nb-7Zr alloy have any influence on bone marrow stromal cells, the source of stem cells, and observe if these metals have properties to induce cell differentiation into osteoblasts. Methods Bone marrow stromal cells (BMSC) were obtained from mice femurs and cultured in osteogenic media without dexamethasone as an external source of cell differentiation. The samples were divided into Ti-35Nb-7Zr alloy (A), pure titanium (Ti), Nb (niobium), and Zr (zirconia) and were characterized by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). After predetermined periods, cell interaction, cytotoxicity, proliferation, and cell differentiation tests were performed. For monotypic biofilm formation, standardized suspensions (106 cells/ml) with the microorganisms S. aureus (S.a) and P. aeruginosa (P.a) were cultured for 24 h on the samples and submitted to an MTT test. Results All samples presented cell proliferation, growth, and spreading. All groups presented cell viability above 70%, but the alloy (A) showed better results, with statistical differences from Nb and Zr samples. Zr expressed higher ALP activity and was statistically different from the other groups (p < 0.05). In contrast, no statistical difference was observed between the samples as regards mineralization nodules. Lower biofilm formation of S.a and P.a. was observed on the Nb samples, with statistical differences from the other samples. Conclusion Our results suggest that the basic elements present in the alloy have osteoinductive characteristics, and Zr has a good influence on bone marrow stromal cell differentiation. We also believe that Nb has the best potential for reducing the formation of microbial biofilms.